The Effect of Problem-Based Learning Model on Mathematics Problem Solving Ability of Class VII Students Junior High School 7 Pematang Siantar - Jesika, Jesika; Sidabutar , Ropinus; Simamora, Rianita (EduMatika: Jurnal MIPA, 2023)
This research aims to determine whether there is an influence of the Problem Based Learning (PBL) instructional model on the mathematical problem-solving abilities of seventh-grade students at SMP Negeri 7 Pematang Siantar. The study employs a quantitative method, specifically a one-shot case study design. The population consists of all seventh-grade students at SMP Negeri 7 Pematang Siantar for the academic year 2023/2024, totaling 288 students. Cluster Random Sampling was used to select a sample, and one class, namely VII-1, was chosen for the study, resulting in a total sample size of 30 students. Data were obtained through a questionnaire measuring students' perceptions of the Problem Based Learning model and a mathematics problem-solving ability test for seventh-grade students at SMP Negeri 7 Pematang Siantar. The instruments utilized included 12 closed-ended statement questionnaires with Likert scale measurements and 5 mathematics problem-solving ability test questions. Following calculations, the conclusion drawn from the simple linear regression analysis with the equation Y’ = a + bX = 27.228 + 0.234X is that the calculated t-value (4.196) exceeds the critical t-value (2.042) at a significance level of 0.00 < 0.05. Consequently, the null hypothesis H0 is rejected, and the alternative hypothesis H  is accepted. The influence of the Problem Based Learning instructional model on the mathematical problem-solving abilities of seventh-grade students at SMP Negeri 7 Pematang Siantar is 38.6%. This implies that the Problem Based Learning model can affect students' mathematical problem-solving abilities by 38.6%, while the remaining 61.4% can be influenced by other factors